P-413 Non-autologous human platelet lysate stimulates in vitro proliferation of primary human endometrial cells from patients with recurrent implantation failure. (30th June 2022) - Nguyen, T.T.T.N; Kwok, Y.S.S; Russell, S; Librach, C
Abstract: Study question: Does patient diagnosis impact induction of primary human endometrial cell proliferation by commercial non-autologous human platelet lysate (HPL)? Summary answer: HPL stimulates in vitro proliferation of both primary endometrial epithelial cells (EECs) and stromal cells (ESCs) from patients with and without recurrent implantation failure (RIF). What is known already: Inadequate endometrial receptivity and thickness are major causes for RIF. Our preliminary results suggested that non-autologous HPL stimulates in vitro proliferation of primary human EECs and ESCs isolated from patients with a history of RIF, with and without a thin endometrium (TE). In addition, using an in vitro model of embryo attachment, we reported that 48-hour treatment with HPL significantly augments the attachment of trophoblast spheroids (generated with HTR-8/SVneo cells) to EECs, suggesting an increase in endometrial receptivity following treatment. This suggests that HPL may standardize future clinical treatments for a TE and endometrial origins of RIF. Study design, size, duration: Endometrial tissue was collected from five patients without RIF (control) and eighteen RIF patients at the CReATe Fertility Centre, Toronto, Canada. The eighteen RIF patients were further classified into three groups (N = 6 each) based on endometrial phenotype: 1) proliferative phase RIF only (without a TE), 2) secretory phase RIF only (without a TE), and 3) secretory phase RIF+TE (with a TE). Primary EECs and ESCs were enzymatically isolated and cultured separately. Participants/materials, setting, methods: Primary EECs and ESCs were serum-starved with serum-free culture media (SFM) for 24 hours and then treated for 48 hours with the following treatment media: SFM (negative control), or SFM supplemented with 1% HPL for EECs, or 10% HPL for ESCs. Cell viability and proliferation were assessed using the metabolic assay PrestoBlue reagent and immunocytochemistry to quantify cells actively expressing the nuclear proliferation marker Ki67. Main results and the role of chance: The metabolic assay demonstrated that 48-hour treatment with non-autologous HPL stimulates a similar significant increase in EEC viability and proliferation for all patient groups. EECs from patients without RIF (control) had the highest fold increase (1.49-fold, P <0.001), followed by proliferative phase RIF only (1.41-fold, P <0.001), secretory phase RIF+TE (1.39-fold, P <0.001), and secretory phase RIF only (1.24-fold, P <0.05). For ESCs, HPL stimulated a significant 2.69-fold increase in cell viability and proliferation for the secretory phase RIF+TE patient group ( P <0.01). Pairwise comparison of the ratio of actively proliferating (Ki67 + ) cells between SFM and HPL treatment revealed that EECs isolated from control patients had the highest and most significant increase by 27.3% ( P <0.05) after HPL treatment. Although not statistically significant, EECs isolated from all RIF patients displayed a similar trend of increased Ki67 + cells after HPL treatment. Whereas HPL treatment significantly increased the ratio of Ki67 + cells for ESCs isolated from both the proliferative phase (by 23.9%, P <0.05) and secretory phase (by 29.9%, P <0.05) endometrium of RIF only patients. Limitations, reasons for caution: Although our data suggests that HPL treatment significantly stimulates primary endometrial cell proliferation in vitro, our sample size per group is small (N = 5-6). A larger sample size and future randomized controlled trials are needed to determine the efficacy of HPL as a treatment for a TE and/or RIF. Wider implications of the findings: Our study provides the groundwork to improve clinical treatment of a TE and endometrial origins of RIF. We anticipate that in addition to stimulating cell proliferation, HPL will also induce a broad transcriptional response towards improved endometrial receptivity. We will next focus on characterizing the transcriptomic profile following HPL treatment. Trial registration number: not applicable